Effect of vitamin D supplementation - Jan Biłogras; Kornelia Karamus; Rafał Rejmak; Martyna Borowska-Łygan; Jakub Tomaszewski; Konrad Strużek; Wojciech Urban (Journal of Education, Health and Sport)
Introduction